The Influence of Influencer Credibility on Purchase Intention of Cosmetic Products (A Study on Followers of the Influencer Tasya Farasya) - Azzahra, Afifah; Roslina, Roslina (Universitas Mercu Buana, 2025)
The rapid expansion of social media has led to the increasing use of influencers in digital marketing. This study examines the effect of influencer credibility comprising attractiveness, expertise, and trustworthiness on consumers’ purchase intention, with a focus on followers of TikTok influencer Tasya Farasya. Data were obtained from 180 respondents using purposive sampling and analyzed through multiple linear regression, t-tests, and the coefficient of determination (R²) using SPSS software. The findings reveal that attractiveness has no significant effect on purchase intention. In contrast, both expertise and trustworthiness significantly influence consumer intentions to purchase cosmetic products. This study contributes to the literature by clarifying which dimensions of influencer credibility drive consumer behavior. The results offer practical implications for the beauty industry in selecting credible influencers and for influencers in maintaining expertise and authenticity to enhance promotional effectiveness.